Legal Compliance in the Implementation of Sharia Savings Loans and Financing Business Activities in Cooperatives - Tarmidzi Tarmidzi; Muhammad Syukron Ni'am; Anindya Aryu Inayati (Al-Hiwalah: Journal of Sharia Economic Law, 2025)
This study analyzes the legal compliance of cooperatives in implementing sharia financing and the role of the Sharia Supervisory Board (DPS) in maintaining compliance with sharia principles, as well as the obstacles faced. This research is an empirical juridical research that reviews the implementation of the Regulation of the Minister of Cooperatives and Small and Medium Enterprises Number 16/Per/M.KUKM/IX/2015 and DSN-MUI Fatwa No. PER-01/DSN-MUI/X/2017. The approach used is a legislative approach. The data in this study was analyzed using a qualitative descriptive method. The results of the study show that the main obstacle faced is the problem of liquidity, especially when there is a massive withdrawal of funds ahead of the holiday, as well as the low understanding of members on the principle of muamalah. Cooperative compliance with related regulations is supervised by DPS and reported to DSN-MUI. However, supervision and education still need to be improved. It is necessary to strengthen liquidity reserves, improve fund disbursement procedures, and continuous training for DPS and cooperative members to improve Islamic financial literacy and the effectiveness of cooperative operational supervision. This research contributes to strengthening the understanding of cooperative law compliance and the strategic role of the Sharia Supervisory Board (DPS) in maintaining sharia compliance and cooperative operational stability, as well as providing practical recommendations for strengthening supervision and education of cooperative members.